Global Perspectives on Labor Migration in Czech Republic : Analysing Drivers, Impacts, and Policy Responses - Tanasiuk, Veronika (2024)
This bachelor's thesis examines the drivers and consequences of global labor migration with a focus on the Czech Republic. It analyzes migration trends, factors contributing to labor migration, and its socio-economic consequences in the Czech Republic as a host country. The study of the theoretical foundations of labor migration provided an understanding of the causes of this process and made it possible to identify factors and drivers of migration, which were considered in the comprehensive integration programs. The use of correlation-regression analysis to determine the impact of economic and socio-cultural factors on the dynamics of labor migration made it possible to identify and assess key factors and take this information into account when developing a strategy for the integration of labor migrants. An analysis of global labor migration trends and best migration policy practices allowed us to propose opportunities for this process in the Czech Republic.